1997
DOI: 10.3758/bf03211330
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of autobiographical memories across the lifespan

Abstract: Words were used to cue autobiographical memories from 20-and 70-year-old subjects. Both groups showed a decrease in memories from the childhood years and a power-function retention function for their most recent 10years. Older subjects also had an increase in the number of memories from the ages 10to 30. These results held for individual subjects as well as grouped data and held when either 124or 921 memories were cued. Reaction times to produce memories were constant across decades except for childhood where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
206
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(239 citation statements)
references
References 40 publications
27
206
2
3
Order By: Relevance
“…Logarithmic curves were previously shown to fit the relation between TD and memory retention, as logarithmic curves characterize the distribution of the correct recall of events from different points in time (Rubin & Schulkind, 1997;Spreng & Levine, 2006). Our data extend these data by showing that cognitive performance (RT with respect to events) was decreasing logarithmically as TDs to the events increased.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Logarithmic curves were previously shown to fit the relation between TD and memory retention, as logarithmic curves characterize the distribution of the correct recall of events from different points in time (Rubin & Schulkind, 1997;Spreng & Levine, 2006). Our data extend these data by showing that cognitive performance (RT with respect to events) was decreasing logarithmically as TDs to the events increased.…”
Section: Discussionsupporting
confidence: 80%
“…We note that this was found for relative-past and relative-future events and thus independent of what time period our participants were asked to imagine as the experimental present time. These behavioral data show that -independently of the imagined self-location in time (past, present, or future) -RTs to life events logarithmically depend on the TD between the imagined self-location in time and the presented life event, demonstrating that TD may play a larger role in self-projection in mental time and episodic thinking (Rubin & Schulkind, 1997;Schroots & Assink, 2005;Schroots et al, 2004;Spreng & Levine, 2006) as previously thought (Addis, Wong, & Schacter, 2007;Arzy et al, 2008;Buckner & Carroll, 2007;Okuda et al, 2003;Szpunar et al, 2007).…”
Section: Methods and Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The initial description of the bump was based on data from several laboratories MEMORY, 2003, 11 (1) Thanks are due to Lone Vasegaard and Karen Randhùj-Andersen for their assistance in selecting subjects, Bernard Jeune for taking part in the planning of the study as leader of``The longitudinal study of Danish centenarians'', and NIA grant RO1 AG16340 which funded the final preparation of the manuscript for publication after the untimely death of Pia Fromholt. reanalysed by Rubin, Wetzler, and Nebes (1986). Since that time there have been consistent findings using the word-cue technique with older adults (Chu & Downes, 2000;Hyland & Ackerman, 1988;Jansari & Parkin, 1996;Rubin & Schulkind, 1997a, 1997bsee Rybash, 1999, and the subsequent articles in his special issue of the Journal of Adult Development for reviews). Minor differences exist in the shape of the distribution with changes in procedure and subject population, but the bump appears repeatedly, even for individuals (Rubin & Schulkind, 1997b).…”
mentioning
confidence: 93%
“…To date, support for this claim lies primarily in evidence suggesting that the life script may partially underlie the reminiscence bump in autobiographical memory (i.e., the greater accessibility in recall of autobiographical events occurring in adolescence and early adulthood, roughly, from 15 to 30 years of age; Rubin & Schulkind, 1997). For instance, Berntsen and Rubin found that the age distribution of life script events features a bump between the ages of 15 and 30 as well.…”
Section: The Cultural Life Scriptmentioning
confidence: 99%